Enzyme Activities in Erythrocytes of Term and Preterm Newborns - Belvisi, Elisa; Bracciali, Carlotta; Ognean, Maria Livia; Tei, Monica; Negro, Simona; Carra, Federica; Proietti, Fabrizio; Buonocore, Giuseppe; Perrone, Serafina; on behalf of the “Gruppo di Studio di Biochimica Clinica Neonatale della Società Italiana di Neonatologia” (Journal of Pediatric Biochemistry, 2016)
The decrease of erythrocyte antioxidant enzyme activity should be considered as a possible cause of hemolysis when there is no evidence of an immune-mediated hemolytic anemia, no consumptive red blood cell disorder, no morphologic or laboratory data to suggest a problem of the red cell membrane, and no evidence of a quantitative or qualitative defect in hemoglobin synthesis. Glutatione has a pilot role in orchestrating the redox balance when there is an excess reactive oxygen species production or defective antioxidant defenses that may have deleterious consequences in various perinatal diseases. Neonatal erythrocytes are a target of extracellular free radicals and in the same time generators of free radicals through Fenton reaction. The complex mechanism underlying the increased oxidative stress susceptibility of neonatal erythrocytes requires further investigation.
Keywords: glutathione; red blood cells; newborn infants; oxidative stress; hemolysis